Pressupostos pedagógicos das atuais propostas de formação superior em saúde no Brasil: origens históricas e fundamentos teóricos - Conterno, Solange de Fátima Reis (2013)
The study approached the pedagogic assumptions of current proposals of health graduation in Brazil, disclosed by the Health Ministry as innovative and as the only possibility, nowadays, of a competent, critical and progressive health graduation. The recommended assumptions are expressed by the quotations of learning to learn; the facilitating professor; signifying learning; teaching centered in the student s interest and problem based learning. Worked with the premise that the assumptions of innovative methodologies if historically situated they lose their inventiveness and originality not constituting themselves in something new. The research aimed systematizing the historical background of the changing movement in graduation of professionals connected to health in the last decades; to identify and analyze the suggestions of changes in health training in different historical moments by different actors. To apprehend from official documents the methodological assumptions divulged to health graduation in Brazil in the last years, aiming to identify the theoretical origins of the identified pedagogical assumptions. For carrying out the present study there were recurred to primary sources, official documents which explicit the reorientations of health professionals training; ordinances; resolutions; reports; recommendations and official discourses elaborated and divulged by institutions, organs and people, which one way or another, are connected to the discussion of professionals formation which act in health field in Brazil and in the world. The secondary sources used in the course of study are intellectual productions identified as disseminators of the movement which encouraged and still do the change in health graduation based in the adhesion of innovative and intellectual methodologies which analyze the limits of active and non-directive assumptions. Through the systematization and analysis of data it was possible to identify the burden that the international movements, mostly those connected to the discussion of medical education and the role of different international organisms as the OPAS and Kellog foundation had in the disclosure of theoretical-methodological change proposes in professional training in the health field. By analyzing the main initiatives of changes in the health training disclosed in Brazil there were explicit the theoretical and political influences which conducted the Health Ministry to induce the proposes of training backed by innovative/active methodologies, which started to divulge the pedagogical assumptions theoretically connected to the active and non-directive pedagogies. Starting from the assumption that not always what is referred as new is new itself, or brings in it a significant progress related to what has been already established, along to the study of the theoretical-methodological origins of the recommended pedagogical assumptions. We conclude that the pedagogical assumptions divulged may be considered innovations in the context in which they were produced, beginning of the last century, because they constitute answers to the problems faced in the field of education, mostly in the beginning of the last century and which had as main point basic education, notedly, children s education. In the field of health, is not something new, but it is strongly anchored in one of the most advanced movements concerning the field, Preventive Medicine, which since the last century has defended the necessity of change, the curricular readjustment and the incorporation of active methodologies in health training. Currently such assumptions are resignified, losing their original sense.